Segregasi Ruang Sosial Antara Pendatang dengan Penduduk Asli pada Permukiman Perkotaan di Denpasar - Syamsul Alam Paturusi (Pusat Kajian Bali Universitas Udayana, 2016)
This article aims to determine the socio-space segregation between newcomers and natives having the same genealogy in Denpasar, Bali. The study was focused on three aspects: determining the factors that influence the occurrence of socio-space segregation; the factors that most influence the shape of such interactions; and its influence on the spatial. The approach taken was descriptive qualitative, through verification at Housing Complex Padang Galeria, West Denpasar. The final result was: bigotry against region of origin, both the migrants and natives became the forerunner to the segregation of socio-space; the most influential factors for the socio-space segregation was customary (pakraman) village institution itself that binds its members in a teritorial unity, spiritual and member togetherness; socio-space segregation phenomena were abstract when transformed into mental maps will show multinodes in the sub-villages in the region of pakraman village.